Superior blood pressure control among hypertensive patients attending specialist clinics in Malaysia - Maskon, Oteh; S, Noorfaizan; SMS, Azarisman; SA, Azreen; I, Saiful Bahri; Abdullah, Aszrin; Omar , Ahmad Marzuki; Ngow, Harris Abdullah; CK, Ting; S , Sapari (2009)
Background The prevalence of hypertension in Malaysia is alarmingly high. The National Survey in 2006 showed 43% of people above 30 years old have hypertension and only 8% reached target blood pressure (BP) of <140/90 mmHg. Among treated patients, only 26% reached target BP. We aimed to evaluate BP control among hypertensives attending Specialist institutions in Malaysia. Methods This prospective study aimed at determining BP control among hypertensive patients attending three specialist institutions in Malaysia located in Kuala Lumpur (KL), Kuantan and Kota Bharu( KB). 950 consecutive patients with known hypertension for at least 6 months were recruited between January 2007 and July 2008. Patients’ demography, BP, cardiovascular (CV) risk factors and medications were obtained. Results A total of 950 patients were recruited. There were more males (n=548, 57.7%) compared to females (n=402, 42.3%). The mean age was 60.9 ± 10.8. The mean Systolic BP (SBP) and diastolic BP (DBP) was 138.8 ± 20.3 mm Hg and 79.6 ±11.4 mmHg respectively. 49.4% of all patients had BP controlled (< 140/90 mmHg) with mean SBP and DBP of 123.2 ± 9.4 mm Hg and 74.2 ± 8.3 mmHg respectively. Males had better SBP control compared to female (SBP 135.9 ± 18.7 vs 142.8 ± 21.7 mmHg, p < 0.001); DBP 77.1 ± 13.7 vs 78.0 + 12.1 mmHg, p = 0.58). Majority of patients were on 2 or 3 antihypertensives (67.6%). BP control among the three centres were consistently good compared to the national figure of 26% (45.1% in KL, 47.1% in Kuantan and 56.3% in KB). Prevalence of CV risk factors was as follows: 54.6% had ischaemic heart disease (IHD), 24.2% underwent coronary revascularization, 50.1% diabetic, 68.7% hyperlipidaemic, 21% smokers and 28% had chronic kidney disease (CKD). Conclusion Tertiary institutions demonstrated much better control of hypertension among their hypertensive patients. Compared to that of national figure, there is a near two-fold difference in the ratio of well controlled BP. Majority of these patients fall into high risk group for CV events, thereby necessitating intensive BP management. This reassuring result suggested the much anticipated